Increasing Work Professionalism In View Of Situational Leadership, Organizational Commitment And Organizational Climate In Bank Sulselbar - Jusri Jusri; Risman Risman; Miko Andi Wardana; I Wayan Eka Sudarmawan; Teguh Setiawan Wibowo (Program Pascasarjana STIE Amkop Makassar, 2023)
Studi ini menguji pengaruh Kepemimpinan Situasional, Komitmen Organisasi, dan Iklim Organisasi terhadap Profesionalisme Kerja. Data dikumpulkan melalui survei, dan analisis regresi berganda dengan uji t dan uji F digunakan untuk pengujian hipotesis. Temuan menunjukkan bahwa Kepemimpinan Situasional, Komitmen Organisasi, dan Iklim Organisasi berpengaruh positif dan signifikan terhadap Profesionalisme Kerja. Uji hipotesis bersama mengkonfirmasi pengaruh bersama mereka. Koefisien determinasi (R2) mengungkapkan bahwa variabel-variabel ini menjelaskan 70,2% variasi dalam Profesionalisme Kerja. Penulis merekomendasikan agar karyawan Bank Sulawesi Barat fokus pada peningkatan Kepemimpinan Situasional, Komitmen Organisasi, dan Iklim Organisasi untuk meningkatkan Profesionalisme Kerja. Kata Kunci: Kepemimpinan Situasional, Komitmen Organisasi, Iklim Organisasi, Profesionalisme Abstract This study examines the impact of Situational Leadership, Organizational Commitment, and Organizational Climate on Work Professionalism. Data was collected through surveys, and multiple regression analysis with t-tests and F-tests was used for hypothesis testing. The findings indicate that Situational Leadership, Organizational Commitment, and Organizational Climate positively and significantly influence Work Professionalism. The joint hypothesis test confirms their collective impact. The determination coefficient (R2) reveals that these variables account for 70.2% of the variation in Work Professionalism. The authors recommend that employees of the Bank Sulselbar focus on improving Situational Leadership, Organizational Commitment, and Organizational Climate to enhance Work Professionalism. Keywords: Situational Leadership, Organizational Commitment, Organizational Climate, Professionalism